STRATEGI GURU DALAM MENGOPTIMALKAN NILAI-NILAI PROFIL PELAJAR PANCASILA PADA PROSES PEMBELAJARAN - Sonia, Anggun; Sofwan, Muhammad; Sholeh, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe teachers’ strategies in optimizing the implementationof the Pancasila Student Profile values and to identify the challenges they face inthe process. The background of this research lies in the importance of charactereducation in shaping morally upright and globally competitive future generations,in line with the spirit of the Merdeka Curriculum. This research uses a qualitativeapproach with a phenomenological method to explore in depth the teachers'experiences in applying these values in the classroom. The research subjectsinclude the homeroom teacher of Class IV A and the principal of SDN 28/IV KotaJambi, with students also involved as supporting informants. Data were collectedthrough observation, in-depth interviews, and documentation. The results showthat the teacher has implemented various teaching strategies reflecting the sixdimensions of the Pancasila Student Profile, such as collaborative projects, groupdiscussions, and contextual value reinforcement in daily learning activities. Valuessuch as mutual cooperation, independence, and critical thinking are instilledthrough creative and participatory approaches. The challenges encounteredinclude limited time, uneven teacher training, and lack of synergy between schooland home environments. Despite these obstacles, the teacher continues to applystrategies consistently and adaptively. This study recommends enhancing teachertraining and strengthening collaboration among stakeholders to support thesustainable implementation of Pancasila Student Profile values.